Syntheses and characterization of two dioxygen-reactive dinuclear macrocyclic schiff-base copper(I) complexes. - Heinemann, Frank Wilhelm; et al. (Inorganic Chemistry, 2003)
The dinuclear copper(I) complex [Cu(2)L(1)(CH(3)CN)(2)](ClO(4))(2) (1, L(1) = 3,6,9,17,20,23-hexaazatricyclo[23.3.1.1]triaconta-1(29),2,9,11(30),12(13),14,16,23,25,27-decaene) has been structurally characterized. As previously described, intramolecular ligand hydroxylation (at the aromatic ring) was observed when 1 was reacted with dioxygen. A stopped-flow analysis of the reaction of 1 with dioxygen under different conditions did not allow a "dioxygen intermediate" to be spectroscopically detected. Detailed NMR and electrochemical data on 1 are also presented and evaluated for the first time. No copper(II) complexes of L(1) could be characterized due to hydrolysis of the compounds. In contrast, complex 2-differing from 1 only in an increase in the size of the chelate rings-did not undergo intramolecular hydroxylation when it was oxidized. The crystal structure of 2 is also described.